UTILIZATION OF TIN EXCAVATION PITS FOR WATER HYACINTH CULTIVATION CULTIVATION IN THE PROVINCE OF BANGKA BELITUNG ISLANDS - Meyzilia, Arvina; Darsiharjo, Darsiharjo (Jurnal Pendidikan Geografi Gea, 2017)
Bangka Belitung Province has large tin excavation pits. Water that fills the large aperture contains harmful metals that are difficult to utilize. To anticipate it, the tin excavation pit can be used as a medium of hyacinth cultivation. This study aims to examine the benefits of hyacinth cultivation in the tin excavation pit. The methods used are survey, literacy study, and documentation. The results show that the tin excavation pit can be used as a medium of water hyacinth cultivation. The cultivation of hyacinth in the tin excavation pit provides several benefits, i.e. (1) absorbing the metal content of Pb and Cd; (2) as biogas material to produce 3,425 MW of electricity; (3) hyacinth can "reclaim" naturally; and (4) as traditional handicraft material to increase economy.